2018
DOI: 10.37190/epe180411
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol and ibuprofen removal from aqueous solutions by ozonation and photochemical processes

Abstract: The comparative experimental study has been performed of removal of pharmaceuticals such as paracetamol and ibuprofen from aqueous solution by ozonation and photochemical degradation in several types of reactors. Ozone, oxygen, and hydrogen peroxide were used as oxidizing agents. Heterogeneous photocatalysis was carried out in the presence of anatase type TiO2 catalyst. To determine the amount of radiation emitted by the UV lamps and transferred into the reactor, chemical feroxioxalate actinometric experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Trousil et al ( 2018 ) also obtained low TOC removal values for IBU degradation, about 20.37% in direct photolysis system and 30.09% in UV/TiO 2 system after 1-h irradiation. The removal of TOC in the oxidation of IBU may be related to the continuous formation of small carboxylic acids during the process (Szabó et al, 2011 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Trousil et al ( 2018 ) also obtained low TOC removal values for IBU degradation, about 20.37% in direct photolysis system and 30.09% in UV/TiO 2 system after 1-h irradiation. The removal of TOC in the oxidation of IBU may be related to the continuous formation of small carboxylic acids during the process (Szabó et al, 2011 ).…”
Section: Resultsmentioning
confidence: 97%
“…Trousil et al reported E EO of 136.2 kWh dm −3 using 11 W power UV lamp in a volume of 20 dm −3 and a concentration of 20 mg dm −3 of IBU in a recirculating reactor. When using the UV/H 2 O 2 system with concentration of 0.5 g dm −3 of oxidant, the energy required for degradation of 90% of the contaminant went to order of 61.2 kWh dm −3 , a 55.1% reduction in energy consumption (Trousil et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In pH 6.0 system TCS obtained 40.63% of TOC removal after 75 min, while for IBU about 10.26% was obtained. Trousil et al (2018) also obtained low TOC removal values for IBU degradation, about 20.37% in direct photolysis system and 30.09% in UV/TiO2 system after 1h irradiation. The removal of TOC in the oxidation of IBU may be related to the continuous formation of small carboxylic acids during the process (Szabó et al 2011).…”
Section: Mineralizationmentioning
confidence: 89%
“…Trousil et al reported EEO of 136.2 kWh dm -3 using 11W power UV lamp in a volume of 20dm -3 and a concentration of 20mg dm -3 of IBU in a recirculating reactor. When using the UV/H2O2 system with concentration of 0.5 g dm -3 of oxidant, the energy required for degradation of 90% of the contaminant went to order of 61.2 kWh dm -3 , a 55.1% reduction in energy consumption (Trousil et al 2018). UV/H2O2 (10 mg L -1 ) pH 6.0 71.26 6.40 UV/H2O2 (5 mg L -1 ) pH 6.0…”
Section: Electric Energy Per Order (Eeo)mentioning
confidence: 99%